Penile Carcinoma: Risk Factors and Molecular Alterations - Marilia F. Calmon; Mânlio Tasso Mota; José Vassallo; Paula Rahal (The Scientific World Journal)
Penile carcinoma is a rare, male cancer. Although the incidence of penile carcinoma is very low in Western countries, in some countries, the incidence is significantly greater, with penile carcinoma accounting for ≤10% of all male malignancies. Greater insight has been gained in recent years as to its pathogenesis, the risk factors associated with its development, and the clinical and histological precursor lesions related to this disease. In this review, risk and conditions factors for penile carcinoma, molecular alterations in this type of cancer, histological types, and prognostic factors will be discussed in order to further our understanding of the biology and behavior of this cancer.